Efektivitas Pembinaan Narapidana Narkoba Pada Rumah Tahanan Negara (Rutan) Kelas IIB Soasio di Kota Tidore Kepulauan - Suratmi Malan; Ilfan Baharuddin; Abdul Wahid Kamma (Peneliti.net, 2023)
Convict coaching is an action to educate, foster, and guide convicts by improving the mindset and behavior as well as the mentality of each convict while serving his sentence. This study aims to determine the effectiveness of fostering drug convicts and the factors that become obstacles to the implementation of the Effectiveness of Guiding Drug Convicts at the Class IIB Soasio State Detention Center (RUTAN) in the City of Tidore Islands. The type of research used is descriptive qualitative by means of field observations, interviews with 9 informants and documentation. development as stated in the Decree of the Minister of Justice No. M.02.PK.0410 of 1990, while the obstacles found in this study include, the lack of budget obtained from RUTAN, lack of infrastructure, lack of coaching staff, low participation of convicts in coaching.